Gaya Bahasa Mahasiswa di Lingkungan Akademik serta Dampaknya terhadap Bahasa Ilmiah - Hasanah, Ulfatul; Lailiyah, Nurul; Nonny Rulisty Putri Sutikno (Jurnal Lentera Edukasi, 2025)
The use of language in the academic environment by students reflects an interesting dynamic, related to the clash between colloquial language and formal scientific language. Scientific language is a formal academic language that requires precision, clarity, and adherence to rules. However, on the other hand, colloquial language is increasingly used by students in daily life, both in direct interactions and through writing on social media, as a form of more relaxed social expression. This writing aims to analyses the trends in students' language styles and their implications for academic interaction. The discussion results show that the use of colloquial language can facilitate social adaptation among peers. However, excessive use of colloquial language can affect students' ability to use standard Indonesian and can impact the quality of scientific wr+6iting and formal communication. Therefore, it is important for students to adjust their language styles according to the context, in order to maintain academic credibility while still being able to build harmonious social relationships.